2012
DOI: 10.1017/s0963548311000605
|View full text |Cite
|
Sign up to set email alerts
|

Large Rainbow Matchings in Edge-Coloured Graphs

Abstract: Arainbow subgraphof an edge-coloured graph is a subgraph whose edges have distinct colours. Thecolour degreeof a vertexvis the number of different colours on edges incident withv. Wang and Li conjectured that fork≥ 4, every edge-coloured graph with minimum colour degreekcontains a rainbow matching of size at least ⌈k Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…LeSaulnier, Stocker, Wenger, and West [11] showed that alwaysα (G) ≥ δ (G)/2 . Exploiting this result and its lemmas, Kostochka and Yancey [9] proved the conjecture of Wang and Li completely:…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…LeSaulnier, Stocker, Wenger, and West [11] showed that alwaysα (G) ≥ δ (G)/2 . Exploiting this result and its lemmas, Kostochka and Yancey [9] proved the conjecture of Wang and Li completely:…”
Section: Introductionmentioning
confidence: 85%
“…We consider t-tolerant edge-colored graphs with n vertices. In Section 2 we construct examples withχ (G) ≥ t 2 (n−1) and prove that alwaysχ (G) < t(t + 1)n ln n. There is potential for improving the upper bound: Kostochka, Pfender, and Yancey [10] showed further that if |V (G)| > 5.5δ(G) 2 , then G has a rainbow matching of size at leastδ(G).…”
Section: Introductionmentioning
confidence: 99%
“…We show that for a strongly edge-colored graph G, if |V (G)| solvable, deciding whether an edge-colored graph has a maximum rainbow matching of size at least k is an NP-Complete problem, mentioned in Garey and Johnson [2] as the Multiple Choice Matching problem. There have been several studies giving lower bounds for the size of maximum rainbow matchings in edge-colored graphs [11,6,5,7]. Rainbow matchings in properly edge-colored graphs were studied in connection with the famous Latin square transversal problem.…”
Section: Introductionmentioning
confidence: 99%
“…From a result of Kostochka and Yancey [5] for arbitrary edge-colored graphs, it follows that if G is a properly edge-colored graph that is not K 4 , then G contains a rainbow matching of size…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation